Resistance, Medicine, and Moral Courage: Lessons on Bioethics from Jewish Physicians during the Holocaust - Wasserman, Jason Adam; Yoskowitz, Herbert (Conatus - Journal of Philosophy, 2019)
There is a perpetrator historiography of the Holocaust and a Jewish historiography of the Holocaust. The former has received the lion’s share of attention in bioethics, particularly in the form of warnings about medicine’s potential for complicity in human atrocity. However, stories of Jewish physicians during the Holocaust are instructive for positive bioethics, one that moves beyond warnings about what not to do. In exercising both explicit and introspective forms of resistance, the heroic work of Jewish physicians in the ghettos and concentration camps tells us a great deal about the virtues and values of medicine. In this article, we frame the stories of four of these Jewish physicians in ways that are instructive for contemporary medicine. By far, the most widely recognized and discussed figure is Viktor Frankl, whose work on hope and the meaning of suffering remains essential insofar as medicine inherently confronts disease and death. Less discussed in bioethics and medical humanities are the cases of Mark Dworzecki, Karel Fleischmann, and Gisella Perl. Dworzecki’s efforts to encourage others in the Vilna Ghetto to document their experiences illustrates the power of narrative for the human experience and the notion of ethics as narrative in the face of suffering. Fleischmann’s art underscores not only the importance of reflective practices for professionals as a form of simultaneous introspection and testimonial, but illuminates hope amid sheer hopelessness. This hope, which was comparatively implicit in much of Fleishmann’s art, is explicated as a method by Frankl, becoming a form of therapy for both physicians wrestling with their professional work, and patients wrestling with their illnesses and diseases. Finally, Perl’s resistance to Mengele’s orders highlights the importance of moral action, not just reflective reaction. The experiences of each of these figures, while certainly located in the unique horrors of Holocaust Germany, portends lessons for today’s physicians faced with moral distress and ethical dilemma in the face of suffering, interpersonal relationships, and socio-political conflicts that increasingly test the professed ideals of medicine. In this article we briefly tell the story of each of these physicians and connect the lessons therein to contemporary medical practice.